Summary of proceedings: Stranded Assets Forum, Waddesdon Manor 14th – 15th March 2014 - Caldecott, B; McDaniels, J; Dericks, G (Smith School of Enterprise and the Environment, 2014)
The University of Oxford's Smith School of Enterprise and the Environment and The Rothschild Foundation held the first Stranded Assets Forum at Waddesdon Manor, Buckinghamshire, on the 14th and 15th March 2014. This report provides a summary of the proceedings and deliberations from the Forum. It outlines the key discussion points and issues that emerged during the sessions held.